COVID 19 and The Emergence of Virtual Tourism in Indonesia: A Technology Readiness Index Perspective - Nono Wibisono; Lina Setiawati; Widi Senalasari (Faculty of Economics, Universitas Sriwijaya, 2022)
For a nation, tourism is a significant source of revenue. However, due to travel bans across the nation and abroad, the pandemic Covid-19 outbreak has had a substantial impact on the tourism business. This study aims to analyze the intention of virtual tourism during the post-pandemic using the technology readiness index and the TPB model (theory of planned behavior). Data was collected from 465 tourist users in Indonesia. The data analysis technique used is structure equational model-partial least square (SEM-PLS). The results proved that all TPB constructs, namely attitudes, subjective norms, and perceived behavior control have a significant effect on the intention to use virtual tourism. The results of this study will help virtual tourism service providers and policymakers in planning services and increasing intention to use virtual tourism in the post-pandemic. The results of the study will add to existing knowledge about the literature on virtual tourism during the pandemic and post-pandemic.